MENYADARKAN PENTINGNYA MENJAGA PERSATUAN DAN TOLERANSI ANTARMASYARAKAT DI WONOSARI, KLATEN SEBAGAI UPAYA MEWUJUDKAN INTEGRASI NASIONAL - Azizah, Annisa Nur; Rohadi, Muhammad; Ghifari, Mi'roju Abdul Rozaq Al; Rahmah, Nika Hidayatur (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
Abstract Indonesia is a heterogeneous country with a diversity of races, religions, ethnicities, tribes and cultures. Countries that have diversity have a great chance of division in society. This makes it a responsibility and challenge for the community in an effort to prevent division. The purpose of this community service activity is to provide information related to the heterogeneous condition of the Indonesian nation, raise awareness in maintaining unity and invite the community to continue to foster mutual tolerance in the community in order to realize national integration. The method of community service implementation is by Interview, music video presentation, and direct discussion. The active role of the community in realizing national integration is very necessary, especially in Wonosari, Klaten. The way to realize national integrase is to not discriminate diversity for example in ethnic, cultural, regional and so on, run the worship in accordance with the beliefs and religions adopted, build awareness of the importance of National Integration, do mutual cooperation in order to increase awareness of society, nation, and state, maintain the unity and unity of the nation, willing to maintain the Unitary State of the Republic of Indonesia, etc.